The philosophical and political thought of Elías Díaz (2013)
The author presents Elías Díaz thought as the perfect conjunction between freedom and equality, with in a differential ethical frame which advocates for a transcendental humanism. Victim of Francoism, Díaz had to suffer the rigors of an unprecedented closeness and achieved with courage and audacity to face the authoritarianism, creating a very authentic theory that it is necessary to remember.